The Resurrected Youth and the Sorrowing Mother: Walter Pater’s Uses of the Myths of Dionysus and Demeter - Anne-Florence Gillard-Estrada (Cahiers Victoriens et Edouardiens)
In the mid-1870s, Walter Pater wrote two essays on Greek mythology, ‘A Study of Dionysus’ and ‘Demeter and Persephone’, in which he wondered about the relevance of Greek myths to the modern mind and advocated empathy with the primitive mind. In these two essays, he explains his method of composition as one of selection, modification and even ‘refinement’ of the material available to him and he chooses indeed certain aspects of those myths in order to emphasize their Dionysiac or their Chthonian elements. However, there is a notable tension between the Apollinian, hellenizing tendency which in these writings is expressed through his insistence on the plastic, ‘humanized’ embodiments of these myths, and between his acknowledgment of darker elements. Pater in fact uses and appropriates these myths in order to deploy varying and opposed discourses centred on the respective figures of Dionysus and of Demeter while reasserting some of the controversial themes put forth in the earlier essays he collected in the Renaissance volume.